Elevated coated-platelets in symptomatic large-artery stenosis patients are associated with early stroke recurrence*. (March 2014) - Kirkpatrick, Angelia C.; Stoner, Julie A.; Dale, George L.; Prodan, Calin I.
<x xml:space="preserve">Abstract</x> Coated-platelets are a subset of platelets with increased procoagulant potential observed upon dual agonist stimulation with collagen and thrombin. These prothrombotic platelets are elevated in patients with non-lacunar ischemic stroke and decreased in patients with spontaneous intracerebral hemorrhage compared to controls. We now investigated coated-platelet synthesis in patients with symptomatic large-artery stenosis and explored the association between coated-platelet levels and stroke recurrence at 3 months in this population. Coated-platelet levels were determined in 60 patients with either acute stroke or transient ischemic attack due to large-artery stenosis and 60 controls. Recurrent stroke incidence at 3 months was stratified by tertiles of coated-platelet levels and compared among groups using a log-rank test. Large-artery stenosis patients had significantly higher coated-platelet levels than controls (mean ± SD, 42.0 ± 15.5% vs. 29.4 ± 13.5%, p < 0.0001). The 3-month cumulative incidence of recurrent stroke was 41% for the highest, 6% for the middle, and 5% for the lowest tertile of coated-platelet levels (p = 0.0045). These results show that elevated coated-platelet levels in patients with symptomatic large-artery stenosis are associated with early stroke recurrence.